Analisis Daya yang Dihasilkan Turbin Angin Tipe Windmill pada Sistem Aerasi Tambak Udang - Nuryanti; Bolo Dwiartomo; Ayi Ruswandi (Jurnal Teknologi dan Rekayasa Manufaktur, 2019)
The Windmil type of Wind Turbine has been developed for aeration system in shrimp developing farm for keeping oxygen concentration equal or above 4 ppm. Wind Turbine would be combined with 2 kW Compressor in order to reduce electric utilities. There are wind energy potential in the location whose wind speed in the range of 0.14 – 8.33 m/s. Six parallel air pumps were attached to wind turbine with stroke length 4 cm. From measurement result Tip Speed Ratio (TSR) 0.9 and Coefficient of Performance 0.31. From this number the power of wind turbine would be defined as 2.2mW – 462 W. If those turbined was combined with 2 kW compressor, electrical utilities would be reduce until 23% for each turbine